Social Mapping: Sustainable Livelihood Approach Karyawangi Village, Pulosari Subdistrict, Pandeglang District - Sumintak, Sumintak; Nurdin, Kamaluddin; Sukirno, Agus; Kurniawan, Ade Fakih; Hunainah, Hunainah (Prosperity: Journal of Society and Empowerment, 2024)
Social mapping is a crucial step in effective community empowerment. This research combines the Asset-Based Community Development (ABCD) framework with the Sustainable Livelihood Approach (SLA) to analyze the potential of community assets in Employeesgi Village, Pulosari District, Pandeglang Regency. The research aims to identify key assets such as natural resources, human capital, social networks, financial capital, and infrastructure to support sustainable development. The research method involved secondary data collection, questionnaires, focus group discussions (FGD) surveys, and purposive sampling techniques with 64 respondents. The research results show that the employee village has good infrastructure assets but faces human and financial capital challenges. Integrating local potential with a targeted development approach produces strategic recommendations, including skills training, financial management, developing nature-based tourism, and improving waste management and transportation access. In conclusion, by optimally utilizing local assets, community empowerment can increase economic resilience and social cohesion while encouraging sustainable development.